Education and socialization of fast food negative impacts in preventing dysmenorrhea on adult women at Prof. Dr. Chairuddin P. Lubis Hospital, Medan, North Sumatra community - Wongso, Venessa; Maya Savira; Eka Roina Megawati; Dedi Ardinata; Milahayati Daulay; Nuraiza Meutia; Yetty Machrina; Selly Azmeila (Journal of Saintech Transfer, 2025)
Dysmenorrhea is a burden on women's health in the world due to its high prevalence. Dysmenorrhea is often associated with several risk factors, one of which is eating habits. The consumption of fast food, which has become a habit of people in the era of globalization, is reported to affect the incidence and intensity of dysmenorrhea. This Community Service aims to socialize the composition and nutritional value of healthy food, the composition and nutritional value of fast food, dysmenorrhea and how it affects daily life as well as the effect of excessive consumption of fast food on dysmenorrhea in the community which was carried out at Prof. Dr. Chairuddin P. Lubis Hospital, Medan, North Sumatra. This community service activity consists of two stages, namely providing education in the form of posters containing material and questions and answers or discussions on related health topics, then handing over the material to the community to be able to practice the knowledge gained so that people's knowledge increases and can be applied to daily life, with the hope that in the future dysmenorrhea disorders caused by excessive fast food intake which causes limitations In carrying out daily activities can be avoided and no longer become one of the largest contributors to health problems in the world and no longer a burden to women's health in the world.